Advances in Citrus Flowering: A Review - Agustí, M.; Reig, C.; Martínez-Fuentes, A.; Mesejo, C. (Frontiers in Plant Science, 2022)
Citrus are polycarpic and evergreen species that flower once in spring or several times a year depending on the genotype and the climatic conditions. Floral induction is triggered by low temperature and water stress, and occurs 2-3 months before bud sprouting, whereas differentiation takes place at the same time as sprouting. The induced buds develop single flowers or determinate inflorescences, so that vegetative growth is required at the axillary buds to renew the polycarpic habit. The presence of fruits inhibits sprouting and flower induction from nearby axillary buds in the current season. In some species and cultivars, this results in low flowering intensity the following spring, thus giving rise to alternate bearing. A number of key flowering genes act in the leaf (CiFT3, CcMADS19, etc.) or in the bud (CsLFY, CsTFL1, etc.) to promote or inhibit both flowering time and meristem identity in respond to these climatic factors, the fruit dominance or the age of the plant (juvenility). Some of these genes can be modified by gibberellin treatments, which reduce bud sprouting and flowering in adult trees, and constitutes the main horticultural technique to control flowering in citrus. This review presents a comprehensive view of all aspects of the flowering process in citrus, converging the research published during the past half century, which focused in plant growth regulators and the nutritional source-sink relationships, and the genetic-molecular approaches published during the present century.